2022
DOI: 10.3390/ijms232113354
|View full text |Cite
|
Sign up to set email alerts
|

Bufalin Inhibits Tumorigenesis, Stemness, and Epithelial–Mesenchymal Transition in Colorectal Cancer through a C-Kit/Slug Signaling Axis

Abstract: Colorectal cancer (CRC) is a major source of morbidity and mortality, characterized by intratumoral heterogeneity and the presence of cancer stem cells (CSCs). Bufalin has potent activity against many tumors, but studies of its effect on CRC stemness are limited. We explored bufalin’s function and mechanism using CRC patient-derived organoids (PDOs) and cell lines. In CRC cells, bufalin prevented nuclear translocation of β-catenin and down-regulated CSC markers (CD44, CD133, LGR5), pluripotency factors, and ep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 59 publications
0
4
0
Order By: Relevance
“…148 Many published studies have confirmed the supportive role of c-KIT in colonic cancer stem cells (CSCs), as it promotes migration, invasiveness, and EMT. 56 , 149 In this context, Ding et al proposed that bufalin has anti-stemness activity by blocking the C-Kit/Slug signaling axis, and therefore it could be a potent treatment for CRC patients. 56 Although c-KIT has been reported in many recently published studies to have an important role in CRC carcinogenesis, imatinib has not yet been approved for the treatment of CRC cases.…”
Section: Colorectal Carcinoma (Crc)mentioning
confidence: 99%
See 2 more Smart Citations
“…148 Many published studies have confirmed the supportive role of c-KIT in colonic cancer stem cells (CSCs), as it promotes migration, invasiveness, and EMT. 56 , 149 In this context, Ding et al proposed that bufalin has anti-stemness activity by blocking the C-Kit/Slug signaling axis, and therefore it could be a potent treatment for CRC patients. 56 Although c-KIT has been reported in many recently published studies to have an important role in CRC carcinogenesis, imatinib has not yet been approved for the treatment of CRC cases.…”
Section: Colorectal Carcinoma (Crc)mentioning
confidence: 99%
“… 56 , 149 In this context, Ding et al proposed that bufalin has anti-stemness activity by blocking the C-Kit/Slug signaling axis, and therefore it could be a potent treatment for CRC patients. 56 Although c-KIT has been reported in many recently published studies to have an important role in CRC carcinogenesis, imatinib has not yet been approved for the treatment of CRC cases. 59 Accordingly, many clinical trials have been performed to assess the therapeutic effect of imatinib on CRC-CMS4.…”
Section: Colorectal Carcinoma (Crc)mentioning
confidence: 99%
See 1 more Smart Citation
“…4 The anticancer mechanism of BFL involves the modulation of multiple signaling pathways, including PI3K/Akt, NF-κB, and Wnt, thereby culminating in suppression of tumor cell growth and metastasis. [5][6][7][8] Additionally, BFL exerts its antitumor effects through mechanisms such as cell cycle regulation, angiogenesis inhibition, and immune modulation. 9,10 Furthermore, bufalin could reverse different tumor cell resistance through multiple mechanisms and have a good synergistic therapeutic effect with other clinical chemotherapy drugs such as cisplatin, paclitaxel, sorafenib and gefitinib.…”
Section: Introductionmentioning
confidence: 99%